Quick team-building activities for busy managers 50 exercises that get results in just 15 minutes - Miller, Brian Cole 1956- (AMACOM, 2015)
Every team needs a regular dose of team spirit to function at its best. That's why managers turn to these easy and effective activities for building camaraderie and cohesion. Now in its second edition, Quick Team-Building Activities for Busy Managers addresses the problems that drag down group productivity and helps teams: Collaborate successfully; Cope with change; Solve problems; Communicate better; Boost creativity; Leverage diversity; Nurture healthy competition; And more.
Includes index. - Print version record
Keywords: Teams in the workplace -- Training of; Group relations training; Communication in organizations -- Problems, exercises, etc; Interpersonal communication -- Problems, exercises, etc; Group games; Relations humaines; Formation; Communication dans les organisations; Problèmes et exercices; Communication interpersonnelle; Problèmes et exercices; Jeux collectifs; Communication in organizations; Interpersonal communication; Teams in the workplace; Training of; Problems and exercises